Citizen-driven innovation: stem cell scientists, patient advocates and financial innovators in the making of the California Institute of Regenerative Medicine (CIRM). (1st December 2014) - Etzkowitz, Henry; Rickne, Annika
Abstract : Our attention in this paper is to the relationship between society and science in science-based innovation processes. We propose that citizens 'and scientists' actions are interlaced and that civil society provides a platform on which novel approaches to innovation may be formed. The empirical focus is set on stem cells and regenerative medicine in California, and the emergence of the California Institute for Regenerative Medicine (CIRM). In an effort to advance the area, a coalition of actors went beyond conventional roles and ventured into a broader realm of 'innovation in innovation', creating a new financial and organizational model. This has played out in a number of interesting and fruitful ways, and implications can be drawn for innovation policy and practice.